USE OF FASCIOCUTANEOUS FLAPS FOR DEFECTS OF LOWER EXTREMITY - V. S. SINGH; J. K. SINHA; V. BHATTACHARYA; F. M. TRIPATHl (Indian Journal of Plastic Surgery)
The fasciocutaneous flaps were raised in 12 patients who had obstinate skin defects in the leg. The undelayed transposition, cross leg and bipedicle advancement fascioculaneous flaps were planned and executed. These are simpler and safer flaps in comparison to myocutaneous and free flaps. A safe length-base ratio is 3:1. The blood vessels in the deep fascia enter through the intermuscular septum. The fascial septal perforators carry the main blood supply to the deep fascia and the overlying skin. Patients with crush injury of the leg with complicated fracture and bruising in the donor area were associated with oedema and haematomas in various surgical planes of the leg. One should be cautious in designing fasciocutaneous flap in such cases.